2010
DOI: 10.1074/jbc.m109.066662
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations in Mitochondrial Dynamics Induced by Human Mutant PINK1 Can Be Rescued by the Mitochondrial Division Inhibitor mdivi-1

Abstract: Mutations in the mitochondrial encoded protein PTEN-induced putative kinase 1 (PINK1) cause autosomal recessive Parkinson disease (PD). In mammalian cells, mutant PINK1 has been reported to promote fission or inhibit fusion in mitochondria; however, the mechanism by which this process occurs remains elusive. Using an ecdysone-inducible expression system in mammalian dopaminergic neuronal cells, we report here that human mutant PINK1 (L347P and W437X) mediates an overall fission effect by increasing the ratio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
156
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(163 citation statements)
references
References 52 publications
7
156
0
Order By: Relevance
“…From the previous study, we expected that the introduction of mdivi-1 could be used as a reliable tool to dissect the exact role of Drp1 throughout myogenic differentiation as it has already proven to be a selective, rapid, and reversible inhibitor of Drp1 with reduced indirect effects as opposed to genetically modified models using mutant, knockout cells, or RNAi techniques (34). Recently, mdivi-1 has emerged as a potential novel therapeutic compound for heart failure, cardiac ischemia-reperfusion injury, pulmonary hypertension, and Parkinson's disease (11,21,34,37,46). While it is too early to be conclusive, the results from our study provide an important insight into a potential adverse effect of mdivi-1 in myogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…From the previous study, we expected that the introduction of mdivi-1 could be used as a reliable tool to dissect the exact role of Drp1 throughout myogenic differentiation as it has already proven to be a selective, rapid, and reversible inhibitor of Drp1 with reduced indirect effects as opposed to genetically modified models using mutant, knockout cells, or RNAi techniques (34). Recently, mdivi-1 has emerged as a potential novel therapeutic compound for heart failure, cardiac ischemia-reperfusion injury, pulmonary hypertension, and Parkinson's disease (11,21,34,37,46). While it is too early to be conclusive, the results from our study provide an important insight into a potential adverse effect of mdivi-1 in myogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe any significant increases in Light Chain 3B (LC3B) staining in permeabilized OT-I T cells, suggesting that autophagic processes are likely not overtly deregulated in these cells ( Figure 3D). We also treated tumor-bearing mice 24 hr after transfer with the mitophagy and mitochondrial fission inhibitor m-divi-1 (Cui et al, 2010); this also failed to improve mitochondrial staining in tumor infiltrating T cells ( Figure 3E). We also asked whether loss of mitochondrial function could occur in vitro in response to co-culture with tumor cells, and found that response of naive or previously activated OT-I T cells to B16 OVA tumor cells in vitro did not result in mitochondrial loss (Figures S3A and S3B).…”
Section: Mitochondria Become Dysfunctional As T Cells Are Activated Imentioning
confidence: 99%
“…Knockdown of Parkin results in mitochondrial elongation in flies (40). However, studies in mammalian cells suggest that loss of Parkin/PINK1 function may lead to excess mitochondria fragmentation or enhanced mitochondrial biogenesis (45)(46)(47)(48). We thus sought to address the molecular details on how Parkin regulates mitochondrial fission and fusion in mammalian systems.…”
mentioning
confidence: 99%